Asuhan Kebidanan Continuity Of Care Ny.R Umur 23 Tahun di Klinik Istika Kabupaten Semarang Jawa Tengah - Linda, Prisma; Veftisia, Vistra (Universitas Ngudi Waluyo, 2023)
Continuous midwifery care (continuity of care), namely providing midwifery care from pregnancy, delivery, postpartum, neonate until the decision to use family planning. This aims to help monitor and detect possible complications that accompany the mother and baby from pregnancy until the mother uses family planning. Midwifery care methods at the Istika Pringapus Clinic, Semarang Regency, Central Java and through home visits. The midwifery care provided to Mrs. In Mrs.